Sumatra Bird Report - Holmes, Derek A (KUKILA, 1996)
All new records of Sumatran birds collected by various observers over the period from 1987 to 1995 that add significantly to the status or distribution as given in the Sumatran checklist (van Marle & Voous 1988) are described. This is the second regional (island) report published by Kukila, the first covering Sulawesi in 1990